A Conceptual Metaphor on the Expression of Apology: A Case Study of the Indonesian Lawyers Club Discussion (A Cognitive Linguistic Study) - Imam Musyayyab; Sailal Arimi (LingPoet: Journal of Linguistics and Literary Research, 2022)
In general, apology used as a way to improve relations between individuals. However, in certain contexts, apology can be used as a political tool that has tendencies based on interests, especially group interests. This is illustrated by the expression of invited guests in the Indonesian Lawyers Club (ILC) discussion with the theme "50 Tahun G30S/PKI: Perlukah Negara Minta Maaf?" which is the object of study in this study. In this research, the researchers use Cognitive Linguistic approach to explore concepts and conceptual metaphors of apology. The researchers use the method of referring to the tapping technique and note to transcribe data which is then classified and analyzed using the matching method. Based on the analysis carried out, conceptually, apologies are understood as a way to calm the feelings of the interlocutor in order to create a more comfortable atmosphere in relations between speakers. In searching for conceptual metaphors, the researchers discover the concept +PERMINTAAN MAAF+ is understood as another concept, some concepts refer to objects, those that refer to abstract entities.